(untitled) (Asian Journal of Agriculture, 2018)
Abstract. Sopialena, Akhsan N, Suryadi A, Nurdiana J. 2018. The identification of soil fungi isolated from Rhizosphere in different varieties of jali plants (Coix lacryma-jobi) in Loa Kulu, Kutai Kartanegara, Indonesia. Asian J Agric 2: 44-47. Rhizosphere effects can indicate the development of an active microbial population around the roots, driving from a loss of organic materials. This research was intended to identify rhizosphere microbes by identifying the potential microbes of four different varieties of jali (Coix lacryma-jobi L.) in Loh Sumber, Loa Kulu, Kutai Kartanegara, Indonesia, i.e., jelai beras, jelai ketan, ketan lekat, and jelai kaltara. The soil samples were collected and isolated in a jali plantation in Loa Kulu, Kutai Kartanegara at 45 days after planting. As many as 16 isolated samples were used, collected from four different varieties of jali and replicated 4 times. The results showed that a variety of microbes at Rhizosphere could be classified as Trichoderma sp., Aspergillus sp., Pythium sp., Fusarium sp., Cunninghamelal sp., and Penicillium sp.